Returns to Inventors - Toivanen, Otto; Väänänen, Lotta (The Review of Economics and Statistics, 2012)
A key input to inventive activity is human capital. Hence, it is important to understand the monetary incentives of inventors. We estimate the effect of patented inventions on individual earnings by linking data on U.S. patents and their inventors to Finnish employer-employee data. Returns are heterogeneous: inventors get a temporary reward of 3% of annual earnings for a patent grant and for highly cited patents a longer-lasting premium of 30% in earnings three years later. Similar medium-term premium's accrue to inventors who initially hold the patent rights, although they forgo earnings at the time of the grant.